Oscillator Compensation Circuit For 27 Mhz - Chan, Yun Huan (Universiti Sains Malaysia, 2017)
A 27 MHz oscillator circuit is designed by using 50nm MOSFET model BSIM 4. It able to generate 27 MHz square wave. This oscillator able to compensate temperature from -25 ̊ C to 80 ̊ C. LTspice software is used to design and run simulation for this circuit. Temperature compensation technique involved cancellation effect of proportional to absolute temperature (PTAT) current source with effect of complementary to absolute temperature (CTAT) current source. Current references circuit is created from temperature compensation technique which able to withstand for temperature range -25 ̊ C to 80 ̊ C without deviation. The current references circuit is used as tail current for differential amplifier. Role of the differential amplifier is becoming an oscillator which able to generate 27 MHz square waves. Tail current of the differential amplifier is major target to be compensated from temperature which helps to maintain output characteristic of the oscillator. Voltage supplied to whole circuit is 1 V. This circuit is able to produce square wave with maximum frequency variation of 6.96% along the temperature range.